PEMIKIRAN GERAKAN TURKI MUDA DALAM UPAYA MENJATUHKAN SULTAN ABDUL HAMID II (1876-1909 M) - Tamara Gissela, Suryo Ediyono (CMES (Center of Middle Eastern Studies), 2017)
The purpose of this research are (1) to find the factors of the Young Turks Movement wanted to attempt the Sultan Abdul Hamid II and (2) to describe the consideration of Young Turk Movement in bringing down Sultan Abdul Hamid II. This study uses qualitative methods presented in descriptive. The technique of data collection was done through the study of library research. Books that became reference were book related to considerations of Young Turk and Sultan Abdul Hamid II. The author did data selection from the rest of the data obtained and then did the analysis. The results of the findings in this research are first, the Young Turks are movement against the reign of Sultan Abdul Hamid II which they regard as dictator. The Young Turk cooperated with liberal opposition to get rid of Sultan abdul Hamid II from his power. Second,the consideration of Young Turk Movement in bringing down Sultan Abdul Hamid II, is build a partnership with Zionism, replacing the Sultan, assault and murder.